PENGEMBANGAN E-MODUL CANVA DAN HEYZINE FLIBOOK BERBASIS GUIDED INQUIRY UNTUK MENINGKATKAN KETERAMPILAN BERFIKIR KRITIS DAN LITERASI LINGKUNGAN DI SMA NEGERI 5 PALU - Winarsi; Darsikin; Muslimin; Kade, Amiruddin; Supriyatman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to develop an e-module based on Guided Inquiry using Canva and Heyzine Flipbook on Thermodynamics material that meets valid, practical, and effective criteria in improving critical thinking skills and environmental literacy of students at SMA Negeri 5 Palu. The research uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subject of the study is a student of class XI M 9 of SMA Negeri 5 Palu. Data were collected through validation sheets, teacher and student response questionnaires, as well as pretest and posttest tests, then analyzed using percentages and N-Gain tests. The results of the study show that the e-modules developed meet he criteria are very valid and very practical. The effectiveness of the e-module is shown by the improvement of critical thinking skills with an N-Gain value of 0.71 (high category) and an increase in environmental literacy with an N-Gain value of 1.08 (high category). The improvement is supported by the implementation of the Guided Inquiry syntax that encourages learners to actively identify problems, investigate, analyze, and draw conclusions, as well as the presentation of interactive materials through Canva and Heyzine Flipbook. Thus, the e-module developed is declared valid, practical, and effective so that it is suitable for use as innovative teaching materials in Thermodynamics learning in high school. Keywords: E-module, Canva, Heyzine, Guided Inquiry, critical thinking, environmental literacy.